Ijarah Contracts From The Time Of Rasulullah To The Present Day - Abdurrahman, Abdurrahman -; Muhajirin, Muhajirin (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
The Islamic banking industry in Indonesia continues to experience significant development. With this development, innovation in products and services in Islamic banking is very important to answer the needs in contemporary banking and financial transactions. One of the many products that have been applied and developed is ijarah. However, practitioners and scholars are still discussing different points of view regarding the legal basis of ijarah and its types. This research aims to review the development process of the ijarah principle and its variance from the early Islamic period to the present. This study is a qualitative research with a literature study approach and library research with descriptive analysis. This research concludes that, The concept of ijarah has existed since the time of the apostle of Allah, namely with the wage system given by the Rasulullah for the services received. For its application in the industry, there are 2 main products, namely Ijarah Muntahiya Bittamlik (IMBT) and Ijarah Maushufah Fi Al Dzimmah (IMDF).